2022
DOI: 10.1108/ejm-10-2020-0764
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dynamic content on visual attention during video advertisements

Abstract: Purpose Dynamic advertising, including television and online video ads, demands new theory and tools developed to understand attention to moving stimuli. The purpose of this study is to empirically test the predictions of a new dynamic attention theory, Dynamic Human-Centred Communication Systems Theory, versus the predictions of salience theory. Design/methodology/approach An eye-tracking study used a sample of consumers to measure visual attention to potential areas of interest (AOIs) in a random selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 118 publications
3
5
0
Order By: Relevance
“…Regarding the smaller visual attention to human faces when individuals were induced to fear, this result agrees with the task relevance theory, reinforced by Wooley et al (2022), which states that when seeing ads, the consumers have the task of checking the advertised product relevance leading to higher visual attention to visual branding presence. Considering that the induction of fear increased the visual attention to the brand name and product packaging, the viewers, when induced to fear, started to prioritize these elements instead human faces in beer ads (attributes less relevant to the ads), resulting in a decreased attention to them.…”
Section: Induction Of Fear Versus Neutralitysupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the smaller visual attention to human faces when individuals were induced to fear, this result agrees with the task relevance theory, reinforced by Wooley et al (2022), which states that when seeing ads, the consumers have the task of checking the advertised product relevance leading to higher visual attention to visual branding presence. Considering that the induction of fear increased the visual attention to the brand name and product packaging, the viewers, when induced to fear, started to prioritize these elements instead human faces in beer ads (attributes less relevant to the ads), resulting in a decreased attention to them.…”
Section: Induction Of Fear Versus Neutralitysupporting
confidence: 85%
“…According to a recent study by Wooley et al (2022), visual branding will be relevant during advertising viewing and will attract visual attention. This phenomenon might occur once when seeing ads, the consumers have the task of assessing the relevance of the advertised product or brand, which contributes to attracting visual attention to visual branding presence (either name, logo, typeface, trademark or pack shot) (Wooley et al, 2022).…”
Section: Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Visual attention is a key aspect of marketing that identifies the subliminal factors that affect the consumers' perception of an advertisement or product (Madan, 2010). Viewers focus less on the central dynamic stimuli as they are present across time and do not require memorization (Wooley et al, 2022).…”
Section: Online Videos and Visual Attentionmentioning
confidence: 99%
“…Compared to self-reported measures, which are subjective and only record conscious, acknowledged opinions, eye tracking has a substantial advantage (Micu and Plummer, 2010). The eye-tracking method measures attention by capturing eye movement to assess advertising efficacy (Wooley et al, 2022). Bialkova et al (2020) showed that brand names are the foremost factor in driving attention, receiving a higher number of fixations.…”
Section: Proposed Model and Hypothesesmentioning
confidence: 99%